Role of laparoscopic appendicectomy in management of early appendicular mass - Ramesh, Kota; Janapareddy, Khyati Kiran (International Surgery Journal, 2020)
Background: Appendicular mass consists of matted loops of bowel and omentum adherent to the adjacent inflamed appendix. Laparoscopic approach adds diagnostic value and allows visualization of entire abdominal viscera facilitating better and safer dissection. Methods: This is an observational prospective study done in patients presenting to Gandhi Hospital’s surgical department with incidentally detected appendicular mass on laparoscopy from August 2016 to August 2018. Results: Maximum cases belong to adolescent age group (13 out of 30). Majority of cases are male patients (24 out of 30). Each surgery took around 1 hour. No intraoperative complications occurred in 23 patients. Difficult adhesiolysis experienced in 5 patients. Serosal bowel injury occurred in 1 patient. Orals were delayed where intraoperative dissection was prolonged or difficult. Majority of patients were discharged after 3 days. Conclusions: With immediate operative management of appendicular mass presenting in early stages of inflammation, dissection can be safely proceeded with and appendicectomy can be safely performed eliminating the need for second hospitalization and risk of recurrence. The incidence of intra-operative and post-operative complications is low making laparoscopic appendicectomy in early appendicular mass a safe and feasible treatment option.